2019
DOI: 10.29255/aksara.v31i1.235.137-152
|View full text |Cite
|
Sign up to set email alerts
|

Factors Hindering the Achievement of English Communicative Competence

Abstract: English communicative competence is one of the prime preferences for learners in this current century, including tourism academy students. As the consequence, learners are equipped by relevant skills including how to articulate English communicative competence insight effectively. Learners are encouraged to fulfill the of micro and macro components of English communicative competence and minimize the factors hindered to be a competent English speaker. The aims of this research were to analyze the factors hinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This research was conducted because the researcher found a gap between the ability of students to be expected in conducting English conversation for service in restaurants and the real conditions of the students, where students' English proficiency for these services is still relatively low. Besides that, this research was also to follow up the research finding published by (Menggo, Suparwa and Astawa, 2019). In terms of hindering factors in the achievement of communicative competence Menggo et.al. found that the most affected factor toward the English communicative competence of the students under the investigation is the insufficiency of practicing English after class with English speaking communities (41,18%).…”
Section: Introductionmentioning
confidence: 71%
“…This research was conducted because the researcher found a gap between the ability of students to be expected in conducting English conversation for service in restaurants and the real conditions of the students, where students' English proficiency for these services is still relatively low. Besides that, this research was also to follow up the research finding published by (Menggo, Suparwa and Astawa, 2019). In terms of hindering factors in the achievement of communicative competence Menggo et.al. found that the most affected factor toward the English communicative competence of the students under the investigation is the insufficiency of practicing English after class with English speaking communities (41,18%).…”
Section: Introductionmentioning
confidence: 71%
“…Competence is demonstrated by how EFL learners perform in presentations, whether linguistically or non-linguistically. Linguistic competence includes phonology, morphology, syntax, and semantics is seen as comprehension of language codes [33], [34]. There are five types of speaking competence: imitative, intensive, responsive, interactive, and extensive.…”
Section: Speaking Competencementioning
confidence: 99%
“…These scientists' conclusions lead us to believe that performance-based assessment has strengthened students' oral skills, both individually and in groups, recognizing holistic language awareness, communication strategies, the courage to talk in front of the class through many teaching techniques, and improved self-confidence, and encouragement to speak English. When this performance-based assessment can be implemented appropriately in a speaking class, college students can gradually understand the micro-linguistic components (morphology, syntax, phonology, and semantics) and macrolinguistic components (communication strategies, functional competence, and discourse analysis) that are often reciprocal in everyday communication (Menggo, Suparwa, & Astawa, 2019).…”
Section: Introductionmentioning
confidence: 99%